Controlled Manipulation of Magic Number Gold–Fullerene Clusters Using Scanning Tunneling Microscopy - Richard Palmer (Langmuir, 2018)
We report controlled manipulation of magic number gold–fullerene clusters, (C60)m–(Au)n, on a Au(111) substrate at 110 K using scanning tunneling microscopy (STM). Each cluster consists of a two-dimensional gold island of nAu atoms confined by a frame of mC60 molecules. Using STM, C60 molecules are extracted from the molecular frame one at a time. The extraction is conducted by driving the STM tip into the cluster, leading to one of the molecules being squeezed out of the frame. Unlike at room temperature, the extracted molecules do not move away from the cluster because of the lack of thermal energy at 110 K; they are found to be attached to the outside of the frame. Reversible manipulation is also possible by pushing an extracted molecule back into the frame. This reversible manipulation is possible only for molecules from the edge of the cluster.